2014
DOI: 10.1128/jb.01359-13
|View full text |Cite
|
Sign up to set email alerts
|

FipB, an Essential Virulence Factor of Francisella tularensis subsp. tularensis, Has Dual Roles in Disulfide Bond Formation

Abstract: FipB, an essential virulence factor of Francisella tularensis, is a lipoprotein with two conserved domains that have similarity to disulfide bond formation A (DsbA) proteins and the amino-terminal dimerization domain of macrophage infectivity potentiator (Mip) proteins, which are proteins with peptidyl-prolyl cis/trans isomerase activity. This combination of conserved domains is unusual, so we further characterized the enzymatic activity and the importance of the Mip domain and lipid modification in virulence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 37 publications
0
24
1
Order By: Relevance
“…However, a separate DsbC protein has not been identified in Francisella strains. We, and others have found that FipB has both oxidoreductase and isomerase activities 13,14 . Recombinant FipB has also been demonstrated to have chaperone activity using an in vitro assay 15 …”
Section: Introductionmentioning
confidence: 93%
“…However, a separate DsbC protein has not been identified in Francisella strains. We, and others have found that FipB has both oxidoreductase and isomerase activities 13,14 . Recombinant FipB has also been demonstrated to have chaperone activity using an in vitro assay 15 …”
Section: Introductionmentioning
confidence: 93%
“…One should argue that the cytoplasm, where interactions in B2H assays take place is reducing environment and that the FTS_1067 must be in oxidized state to act as an oxidoreductase or isomerase. But as was mentioned above, the results of our group [3] and the results by Qin et al [1] indicate that both oxidoreductase and isomerase activities of FTS_1067 or FTT_1103 are dependent on their reduced state and thus, the reducing environment in cytoplasm should not be limiting.…”
Section: Discussionmentioning
confidence: 65%
“…Recently, it was shown that both FTS_1067 and FTT_1103 proteins need to be reduced to act as an isomerase or oxidoreductase [1,3]. Due to this fact, we decided to further validate the observed protein-protein interactions by using an independent approach, the B2H systems where the interactions take place in reducing cytoplasm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations